PENGGUNAAN BAHASA PADA IKLAN LUAR RUANG DI KOTA PONTIANAK - Anriani Anriani; Ahmad Rabi ul Muzammil; Agus Syahrani (Universitas Tanjungpura, 2019)
AbstractThe background of this research was because the outdoor advertising is information tool for general public that located at public place, such main street that often passed by people and around people. The method in this research was descriptive method. The research form was qualitative research. The data of this research was outdoor advertising at Pontianak. The outdoor advertising was analyzed from physical aspects, language aspects, and structure of advertising text. Data analysis it showed that the use of language on outdoor advertising in Pontianak from physical aspects on advertisement was relatively large, the used material was not permanent, the advertising location was strategic, and gave big impact on the use of people language. Based on the language aspects, the use of spelling mostly had errors on word usage and punctuation, word choice or diction had errors in the lack of words usage accuracy, and the use of sentence structure was good enough. The structure of advertising text was already fulfilled the correct advertising character which consists three parts such title, explanation, and the address and name of the adviser. Keywords:the use of language, outdoor advertising, Pontianak